2012
DOI: 10.1111/bjep.12001
|View full text |Cite
|
Sign up to set email alerts
|

Achievement goals in adult learners: Evidence from distance education

Abstract: The achievement-goal framework is as appropriate for understanding influences on attainment in adult learners as it is in younger students. Adult learners may be more sensitive to the deleterious effects of adopting mastery-avoidance achievement goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 80 publications
1
12
1
Order By: Relevance
“…The relationship between goal orientation and academic performance in adult distance education has hardly been studied before, with the exception of the research of Remedios and Richardson (2013). The present study partly replicates their findings, as they also found performance approach to be a positive predictor and performance avoidance to be a negative predictor of exam grades.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…The relationship between goal orientation and academic performance in adult distance education has hardly been studied before, with the exception of the research of Remedios and Richardson (2013). The present study partly replicates their findings, as they also found performance approach to be a positive predictor and performance avoidance to be a negative predictor of exam grades.…”
supporting
confidence: 87%
“…To our knowledge, the research of Remedios and Richardson (2013) is the only study in which the relationship between goal orientation and academic achievement for adult students in a distance education setting was examined. Remedios and Richardson found a positive relationship between performance approach and examination grades and a negative relationship between mastery avoidance and performance avoidance with examination grades.…”
Section: Goal Orientation and Academic Performance In Distance Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Sachs (2001) found that mastery goals predicted adult learners' enjoyment in completing course assignments but not their graded performance. More direct support regarding the significant role of mastery goals for distance learners can be derived from several recent studies (Ng, 2006(Ng, , 2008(Ng, , 2009Remedios & Richardson, 2012) that produced repeated empirical evidence supporting that learning for knowledge improvement, understanding and competence development have been dominant forms of motivation for this group of learners. However, the extent to which mastery goals are the sole motivational source for distance learners is questionable.…”
Section: The Current Studymentioning
confidence: 99%